Osteoblast differentiation is enhanced by a nano-to-micro hybrid titanium surface created by Yb:YAG laser irradiation - Mariscal-Muñoz, Eduardo [UNESP]; Costa, Carlos A. S. [UNESP]; Tavares, Hewerson S. [UNESP]; Bianchi, Jonas [UNESP]; Hebling, Josimeri [UNESP]; Machado, João P. B.; Lerner, Ulf H.; Souza, Pedro P. C. (Springer, 2015)
The aim of this study was to analyze the capacity of a new modified laser surface to stimulate calvarial osteoblasts isolated from neonatal mouse bones to differentiate and form mineralized nodules. Titanium discs were subjectezd or not to laser irradiation according to specific parameters and characterized. Osteoblasts isolated from neonatal mouse calvaria were cultured over the discs, and the capacity of these cells to proliferate (MTT assay), form mineralized nodules (Alizarin red assay), and enhance alkaline phosphatase activity (ALPase activity) was analyzed. Real-time PCR was used for quantification of gene expression. Laser-irradiated titanium discs (L) presented a rough nano-to-micrometric oxidized surface contrasting with the smooth pattern on polished discs (P). The Ra on the micrometric level increased from 0.32 ± 0.01 μm on P surfaces to 10.57 ± 0.39 μm on L surfaces. When compared with P, L promoted changes in osteoblast morphology, increased mineralized nodule formation in osteoblasts cultured on the surfaces for 14 days, and enhanced ALPase activity at days 7 and 14. Transcription factors triggering osteoblast differentiation (Runx2 and Sp7) and genes encoding the bone extracellular matrix proteins collagen type-1 (Col1a1), osteopontin (Spp1), and osteocalcin (Bglap) were upregulated in cells on L surfaces compared with those on P surfaces at days 1-14. Laser treatment of titanium surfaces created a rough surface that stimulated osteoblast differentiation. Laser treatment of titanium generates a reproducible and efficient surface triggering osteoblast differentiation that can be of importance for osteointegration.
Keywords: Titanium implants; Osteoblast; Bone; Laser